The Diplomat-Scholar A Biography of Leon Ma. Guerrero - Fernandez, Erwin S. ([S.l.] : ISEAS - Yusof Ishak Institute, 2017)
Leon Ma. Guerrero (1915-82), a top-notch writer and diplomat, served six Philippine presidents, beginning with President Manuel L. Quezon and ending with President Ferdinand E. Marcos. In this first full-length biography, Guerrero's varied career as writer and diplomat is highlighted from an amateur student editor and associate editor of a prestigious magazine to ambassador to different countries that reflected then the exciting directions of Philippine foreign policy. But did you know that he served as public prosecutor in the notorious Nalundasan murder case, involving the future Philippine.
The Diplomat-Scholar: A Biography of Leon Ma. Guerrero -- Dedication -- Contents -- Preface -- Prologue -- Chronology -- I. Ermita and Santa Cruz to Intramuros: Between Literary and Legal Career -- 1. Bourgeois Ermita: Birth and Boyhood -- 2. Education under American Jesuits -- 3. The Humorist as Critic, Writer and Actor -- 4. Juggling Law and Journalism on the Eve of War -- II. To Tokyo and Back: The Making of a Diplomat -- 5. The Assistant Solicitor -- 6. From Intelligence Officer in Bataan to the Return of Ignacio Javier -- 7. Second, then First Secretary -- 8. At the Home Office: The Diplomat as Historian -- III. Going In, then Out of the Political Jungle: Padre Burgos to Arlegui -- 9. The Legal Counsel, Professor and Translator -- 10. The Foreign Policy Critic and Spokesman -- 11.'Asia for the Asians' or How to Leave Arlegui in Six Months -- IV. London and Madrid: The Philippines in a Resurgent Asia -- 12. At the Court of Saint James -- 13. A Verbal Tussle in the UN -- 14. The Biographer -- 15. At Franco Country -- 16. In Search of the Burgos Trial Records -- 17. Home Leave in Preparation for a State Visit -- V. New Delhi to Belgrade: The Philippines towards Non-Alignment -- 18. Homecoming to Asia at Nehruvian India -- 19.'Diplomacy of Development' and Other Speeches -- 20. The Foreign Policy Rescuer and Again, Critic -- 21. The Diplomat as Efficient Intellectual-Bureaucrat -- 22. Endorsing Non-alignment amid Personal Crisis -- 23. Flirting with Dictators -- 24. Martial Law Propagandist -- 25. At Tito's Pre-Balkanized Yugoslavia -- Epilogue -- Glossary -- List of Abbreviations -- Bibliography -- Index -- About the Author -- Photo Section.
Includes bibliographical references and index.
Keywords: Historical, Political and Military